2019
DOI: 10.1111/sjop.12592
|View full text |Cite
|
Sign up to set email alerts
|

Pain appraisal and quality of life in 108 outpatients with rheumatoid arthritis

Abstract: Individual differences in emotional functioning, pain appraisal processing, and perceived social support may play a relevant role in the subjective experience of pain. Due to the paucity of data regarding individuals with Rheumatoid Arthritis (RA), the present study aimed to examine pain intensity, emotional functioning (psychological distress and alexithymia), pain appraisal (pain beliefs, pain catastrophizing, and pain‐related coping strategies) and social support, and their relationships with the health‐rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 82 publications
(121 reference statements)
2
9
0
1
Order By: Relevance
“…Similar to earlier studies, 13 14 15 16 we reported positive association of QOL with education, social support, and physical functions, negative association of QOL with pain, disease activity, maladaptive coping (internalization), and psychiatric morbidity and no association was found with age, gender, and duration of illness. On the contrary, other studies 3 14 reported lower QOL in female and older patients.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to earlier studies, 13 14 15 16 we reported positive association of QOL with education, social support, and physical functions, negative association of QOL with pain, disease activity, maladaptive coping (internalization), and psychiatric morbidity and no association was found with age, gender, and duration of illness. On the contrary, other studies 3 14 reported lower QOL in female and older patients.…”
Section: Discussionsupporting
confidence: 89%
“…The result of our study also indicated that pain catastrophizing partially mediated the relationship between insomnia and HRQoL. Previous studies have shown that pain catastrophizing was a risk factor for HRQoL (Larice et al, 2020;van Aken et al, 2017). However, to our knowledge no studies have explored the effect of insomnia on pain catastrophizing, much less the mediating effect of pain catastrophizing in the relation between insomnia and HRQoL.…”
Section: Discussionsupporting
confidence: 67%
“…Pain catastrophizing has been observed in individuals with FM [ 40 ] and has been robustly associated with physical impairment in FM and other pain conditions [ 41 , 42 , 43 , 44 ]. However, the role of pain catastrophizing in individuals with chronic pain conditions and comorbid obesity remains less clear.…”
Section: Introductionmentioning
confidence: 99%